Politics, ideology and nationalism : Jinnah, Savarkar and Ambedkar versus Gandhi - Chakrabarty, Bidyut (New Delhi Sage Publication, 2020)
"Politics, Ideology and Nationalism: Jinnah, Savarkar and Ambedkar versus Gandhi is a new argument based on familiar historical evidences. It discusses three leaders-Savarkar, Ambedkar and Jinnah-in their opposition to Gandhi both in terms of ideology as well as social and political discourse. Although there are biographical works and other notable publications on them, none of these attempt to engage in contrasting their ideology and practices on a common platform. This book examines Gandhi and Savarkar-Ambedkar-Jinnah's commonality of opposition and their differing ideas of modernity. All three of them saw Gandhi as the biggest hurdle to the projects that they conceived. The book explores how these differences went beyond politics and shaped the contours of Indian politics during the 1930s and 1940s, and continue to affect it even today"--
Includes bibliographical references and index.
Keywords: Gandhi; Savarkar, Vinayak Damodar; Ambedkar, B. R; Jinnah, Mahomed Ali; Identity politics; Nationalism; India